Slovenology - Charney, Noah (knjige, 2020)
Slovenology is part memoir, part essay collection, part travel writing, and part guidebook. It is meant to act as a guide-in-hand while visiting Slovenia, but it can be read just as well from the comfort of your own home to give you a deeper and more colorful sense of what it’s like to live in this remarkable, little-known country.
Keywords: Američani; Charney, Noah; V leposlovju